GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 565968519 species occurrences available in GBIF matching the query: All data. The dataset includes 565968519 records from 13247 constituent datasets: 1 records from Tunicata ZMK. 4702 records from Amphibian specimens. 63504 records from UNSM Vertebrate Specimens. 52181 records from ANTARCTIC PLANT DATABASE. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 511 records from Coleoptera of Swierklaniec Forest. 98 records from Rund ums Cani. 78 records from Birdrace-Die_Laufenten-Braunschweig. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 6 records from Wiese. 6 records from Nannofossil abundance of Hole 67-494A. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 127133 records from Fish specimens. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 126 records from Total foraminifera counts of multinet M11/1_MSN517. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 11 records from Microzooplankton abundance and biomass at station TT043_17-1. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 1470 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 108-662A. 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 7410 records from Helgeland Museum, Lepidoptera. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 91 records from Birdrace-Enger_am_Spektiv-Herford. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 13 records from FND "Weißer Berg" Leißling. 15 records from Kirchheller Heide ( Bottrop). 11 records from Microzooplankton abundance and biomass at station TT045_4-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-37-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 20 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 182 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 62 records from Abundance of coccosphere-units of sediment core GIK23400-3. 255 records from Planktic foraminifera counts of sediment core RC09-150. 31 records from Aktionstag Wiese am Vogelhammerkopf. 3709 records from Plant (MNHM-PL). 16604 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 20 records from Distribution of planktonic foraminifera and other biogenic components in ODP Hole 113-693A (Figure 2). 565 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_2. 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 702 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 2427 records from Ibaraki Nature Museum, Mollusk collection. 321 records from Nova Scotia Department of Natural Resources, Subenacadie, NS, Canada. 354 records from Foraminifera distribution of sediment core KS310. 85 records from Unterbrucker Weiher. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D4. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 3324 records from Crustacea collection of the Finnish Museum of Natural History. 290333 records from AMNH Mammal Collections. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 398 records from Tsetse flies of East Africa update. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 36 records from Salzwiese Diekskiel. 79 records from Plasm bearing foraminifera counts of multinet M21/2_MSN628. 136 records from Total foraminifera counts of multinet PO247/2_MSN1380. 5 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_818-16. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-7. 12 records from Distribution of meiobenthos in sediment core M19_239-2 of the northeastern Atlantic (Table 1). 45 records from Nannofossil abundance of Hole 64-481A. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 368 records from Great Lakes Forestry Centre Insect Collection. 36254 records from Fish collection of National Museum of Nature and Science. 19164 records from The Gordon Alexander Orthoptera Collection. 1684 records from MfN Fish Collection, Zoology. 3 records from Analyses of the recent components of sediment core PS1215-2. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 195 records from Altenburg bei Bamberg. 181 records from Occurrence of mammalia relicts at site Kemathenhöhle. 19 records from Occurrence of mammalia relicts at site Gröbern. 4 records from Occurrence of mammalia relicts at site Ahlen. 808 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 48 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 169 records from Whale log - observations from ANARE voyages. 1740 records from Monitoring data from the federal state Berlin (Germany). 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 317 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - iSpot (2008-2010): Shieldbugs & allied species. 6943 records from DMNS Egg Collection (Arctos). 218 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 5570 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 1358 records from Electron Micrograph Database (Australian Antarctic Data Centre). 46156 records from Zooplankton in the bay of Biscay (1995-2004 Yearly spring DEPM surveys). 399 records from Colecciones Zoológicas de la Universidad de León, Colección de Poliquetos. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 160757 records from Slovenian Fungal Database - Boletus informaticus. 43 records from Vogelstimmenführung durch den Tiergarten. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D4. 22 records from Occurrence of mammalia relicts at site Castlepook Cave. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 123 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 17 records from Benthic foraminifera abundance of Hole 11-108. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 1460 records from Range table from benthic foraminifers in ODP Hole 151-909C. 631 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 176 records from (Appendix E) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 161-976C. 1320 records from (Table 8D) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 15-4 through 19-3. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 2546 records from The atlas of butterflies in Kraków. 4390 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 1 records from Hoplophora decumana. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 128 records from Total foraminifera counts of multinet M42/3_MSN1359. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_10-CTD124. 16 records from Phytoplankton abundance at station Sechin_2003-12-03_1, Casma, Peru. 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 50 records from Leben in den Elbwiesen. 16 records from Nannofossil abundance of Hole 11-106B. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 66 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 113-689. 394 records from (App 7) Relative contents of benthic foraminifera species in sediments accumulated during last 1000 years, Core ASV11-987. 700 records from (Table 3c) Foraminiferal distribution chart of ODP Hole 122-762C. 7 records from Collection Malakologie - SMNG. 18473 records from Australian Antarctic Division Herbarium. 802 records from Biological Collection, National Institute of Oceanography, Goa, India. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 240 records from Coleoptera identified from the Woolwich Manor Way site, Becton, London. 40 records from Coccolith counts of multinet M32/5_MSN979. 18 records from Nannofossil abundance of Hole 8-73. 75 records from Planktic foraminifera counts of sediment core V26-124. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 4540 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 3524 records from Escarabajos y moscas de los bosques de niebla del sureste mexicano (Coleoptera: Scarabaeoidea; Diptera: Syrphidae y Calliphoridae). 4380 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 12836 records from Planktic foraminifera assemblage in sediment core MD97-2142. 16 records from Occurrence of mammalia relicts at site Dorog. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 1790 records from Planktic foraminifera abundance of Hole 9-77B. 62371 records from MLZ Bird Collection (Arctos). 132 records from Range table from benthic foraminifers in ODP Hole 144-876A. 3201 records from Weevils of the Carpathians. 13325 records from Herbier du Bénin. 19 records from Goethe-Hauptschule/Projekt I-10. 19386 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 2 records from Akita Prefectural Museum＋Hagfishes Specimens of Akita Prefectural Museum. 62 records from Phytoplankton abundance during Akademik Vernadsky cruise AV22. 3538 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 13960 records from Collection Trichoptera - SMF. 21172 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 6629 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 33883 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 495 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 85 records from Schulgelände IGS Kaufungen. 376 records from Planktic foraminifera abundance of Hole 22-216. 1845 records from (Table 8C) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 8-5 through 15-3. 69 records from Planktic foraminifera abundance of Hole 52-418. 427 records from Planktic foraminifera abundance of Hole 76-533A. 691 records from Foraminifera abundance of Hole 24-236. 1035 records from Foraminifera abundance of Hole 24-237. 1289 records from Percentages of planktonic foraminifera species in sediment core V22-222. 27 records from Herbarium Senckenbergianum (FR) - Protista. 1304 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 83 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 98 records from Planktic foraminifera abundance of Hole 74-528. 130 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 16344 records from Coleccion de sonidos ambientales. 534 records from Leopard Seal census, Heard Island 1987/88. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 1 records from Orthoptera - SMF. 621 records from Biological Records Centre - UK Ladybird Survey data from iRecord. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 781 records from RSPB - Bittern Annual Surveys in Britain 1990-2008 (SCARABBS). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 1364 records from Irish Collembola records. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 166 records from BIRDRACE Die Düsselmöwen. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 149 records from Total foraminifera counts of multinet PO247/2_MSN1372. 337366 records from British Lichen Society - BLS Lichen Database: England. 1 records from Dinoflagellate abundance of Hole 19-183. 38 records from Dinoflagellate abundance of Hole 71-512. 811 records from Amphibians and reptiles of Ireland. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 8 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 26 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thinocoridae. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 1470 records from EDIT - ATBI in Spreewald (Germany). 60 records from (Table 5) Quality control of palynoclasts, palynomorphs and microplankton abundances in ODPHole 112-686B. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 683018 records from The System-wide Information Network for Genetic Resources (SINGER). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 19 records from Antarctic Krill occurrence data from Japanese expeditions. 30 records from A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia.. 205 records from Planktic foraminifera abundance of Hole 29-284A. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 109 records from Dreilinden Gymnasium-Schulgelände. 3536 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 320 records from Scottish Wildlife Trust - Ants: Formica Exsecta Records from Abernethy RSPB. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 10271 records from Carabidae of Poland. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 10234 records from Collection entomologique Barthélémy. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 27 records from Total foraminifera counts of trap L3_92_45. 268 records from Geometry of coccolith Coccolithus pelagicus in sediment core PS1113-1. 14 records from Ostracoda abundance of Hole 44-392A. 45 records from BIRDRACE Ohne Graureiher läuft nix!. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 49406 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 13427 records from CNPE/Coleccion Nacional de Peces. 22367 records from Bird Collection. 48 records from Relative abundance of planktic foraminifera in sediment core K11. 60 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 38 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 4 records from Occurrence of mammalia relicts at site Henauhof NW 2. 152 records from Planktic foraminifera abundance of Hole 16-159. 99 records from Streuobstwiese Stedar. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 8 records from Little known Orphninae (Coleoptera, Scarabaeidae) collected by the Madagascan expeditions of the California Academy of Sciences. 3139 records from (Appendix A) Agglutinated foraminifers in ODP Hole 123-765C. 4 records from Akita Prefectural Museum＋Specimens of Class Maxillopoda of Akita Prefectural Museum. 6627 records from ATCC Fungi Collection Catalog. 1101 records from Relative abundance of ostracods in sediment core Co1202. 122 records from Occurrence of mammalia relicts at site Hunas. 2240 records from Derbyshire Biological Records Centre - Hemiptera Records 1969 - 2011. 55690 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 96 records from Birdrace-federleser-Herford. 144 records from Ehmkendorf. 83 records from Foraminifera species abundances from tow TT011_7-MOC66. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 34 records from (Table 6B) Distribution of Mesozoic nannoliths at DSDP Hole 43-387. 129 records from Dinoflagellate cysts from sediment core PS2458-4. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 74 records from Faunal assemblage of sediment core TR149-36. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_15-CTD175. 1045745 records from Herbarium of The New York Botanical Garden. 12 records from Nannofossil abundance of Hole 31-299. 5538 records from Colección Alberto Tinaut (Formicidae). 2000 records from Shellfish (ASJK_MS). 45 records from Collection Bryozoa - ZIM Hamburg. 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 4641 records from Lepidopterists Society Season Summaries 1973-1997. 191859 records from herbario. 894 records from CNAN/Arañas sinantrópicas. 12 records from Microplankton abundance at bottle station SEPT-1999-K1. 122 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 14 records from Radiolaria assemblage in sediment core GIK23259-2. 2444 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 26079 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 169278 records from herpetology. 1428 records from (Fig. 14) Distribution of dinoflagellate cysts in Early Cretaceous sediments of ODP Hole 103-638B in the North Atlantic. 893 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 2 records from Ireneopone gibber (Hym., Formicidae), a new genus and species of myrmicine ant from Mauritius.. 162150 records from Ditsong Museum. 854 records from (Table T1) Abundance of stratigraphically important planktonic foraminifera in ODP Site 186-1150 sediments. 35 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 1444609 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 1594 records from Musée Vert ornithology collection. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 881 records from (Table 2) Planktic foraminifera and their diversity indices of sediment surface samples from the Atlantic Ocean. 4 records from "Am Riedert" im Westerzgebirge. 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 14 records from Benthic macrofauna abundance of sediment core 12930-081. 202 records from Dinoflagellate cysts from sediment core PS1295-4. 1000 records from Diplopoda (JJHA-DI). 22 records from Sediment properties of core PLG95B_01BOXG. 1077 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 12 records from (Table 3) Miocene biostratigraphy of the Hemmorian stage in Schleswig-Holstein. 104431 records from Field Museum of Natural History (Zoology) Fish Collection. 8162 records from CRI - Herbário Pe. Dr. Raulino Reitz. 994 records from Biological Records In Essex - Bat records for Essex from 1971 - present.. 8540 records from Herbarium WRSL, Lichens Collection. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 61 records from Total foraminifera counts of multinet M10/2_MSN229. 46 records from Phytoplankton abundance at station DI183_11872#3. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 3161 records from Census in Agrimey forest reserve (southern Benin). 85 records from Epifauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 37 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 2 records from Nannofossil abundance of Hole 6-50A. 79 records from Ostracoda abundance of Hole 34-319. 13 records from Nannofossil abundance of Hole 11-103. 118 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 61010 records from Fish Collection of Hokkaido University. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 279 records from (Table 3) Relative abundance of benthic foraminifera in ODP Hole 112-681A. 40 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE272. 2418 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 1399 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-182. 4 records from Occurrence of mammalia relicts at site Grotte Cotencher. 12 records from New data on the European species of three genera Scelionidae (Hymenoptera).. 8 records from Planktic foraminifera abundance of Hole 94-611B. 175 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 2 records from Abundance of benthos infauna at station GIK23024-1. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 114 records from Flora. 62 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/553-11. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 4 records from Trap data WR2, 1648 m. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 215 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 361 records from Water mite collection of Pauli Bagge. 38 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 156 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 1513 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 23146 records from BC Coastal Waterbird Survey. 3578 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009 â sensitive records. 10203 records from Coleoptera specimen database of Osaka Museum of Natural History. 305 records from Flux data of NU2_trap (Table A1). 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 123 records from Birdrace-SportfreundeTriller-Münster. 297 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 39 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 11 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 5 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 114203 records from UTA Herpetology. 2 records from Planktic foraminifera abundance of Hole 54-421. 229 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 279 records from Range table from planktonic foraminifers in ODP Hole 175-1077A. 59928 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 8008 records from Avistajes de espcies de valor especial en reas protegidas del noreste de Argentina. 4 records from Sächsische Schweiz (Wehlener Gebiet). 1973 records from Foraminifera abundance of Hole 61-462. 10 records from Oberservation of birds at station PS14/157 along 49° West. 2737 records from Gunma Museum of Natural History, Molluscan Specimen. 20 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto20-28. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 3 records from Res Ligusticae XXII. Diagnosi di nuove specie di miriapodi cavernicoli. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 457 records from Microbial Observatory of the Laboratoire Arago. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 177 records from BIRDRACE Die Kielbris. 9 records from A new species of Pseudobagrus (Teleostei: Siluriformes: Bagridae) from southern China.. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 720 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 126-793A. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 192425 records from Bryophytes of Ireland. 1833 records from DSMZ Fungi. 9647 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 1 records from Karpfenteich, Klasse 6d. 163 records from Benthic foraminifera and nannofossil abundance of Hole 40-364. 2066 records from Range table from benthic foraminifers in ODP Hole 159-959D. 78 records from Microfossil abundance of Hole 21-206. 139 records from Siliceous microfossil occurrence, Site 177-1093. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 12065 records from Tromsø Museum, Bryophytes. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1035 records from National Museum Of Marine Science & Technology. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 49 records from Dörnberg. 82 records from Plasm bearing foraminifera counts from M35/1_MSN1050. 164 records from Plasm bearing foraminifera counts from M35/1_MSN1064. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 31 records from Planktic foraminifera of sediment core GeoB1406-4. 39 records from Sedimentological investigation on core V25-56. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 6 records from Microzooplankton abundance and biomass at station TT043_7-20. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 159 records from Phytoplankton abundance at station CD47_0606C#7. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 269 records from BIRDRACE speedbirder. 371 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001H. 1 records from Nouvelles fourmis d'Afrique.. 4649 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 3182 records from Finnish Entomological Database: Heteroptera. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 69 records from Entdeckertour am Muldestausee 1/05. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 77 records from Distribution of planktonic foraminifera of sediment core SH1972_1. 112 records from Werl macht sich auf die Suche. 213 records from Coccoliths in sediment core PS1113-1. 4 records from Nannofossil abundance of Hole 8-75. 821 records from Planktic foraminifera counts of sediment core V19-188. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 103 records from Mammals (UWEP-MM). 78 records from Mammals (GNHM-MM). 2109 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 240 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 1 records from Oribates angulatus. 6 records from Ostracoda abundance of Hole 13-134. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 3189 records from Propuesta para la realización de 37 fichas biológicas de las especies de herpetofauna incluidas en la NOM-059 presentes en la Península de Yucatán. 80 records from Collection Copepoda - SMF. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 120 records from Total foraminifera counts of multinet PO247/2_MSN1387. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 418 records from Fossil (GNHM-FO). 4 records from Description of lithologic section units of IODP Hole 325-M0034A. 90 records from Planktic foraminifera abundance of Hole 24-233A. 709 records from Range table from benthic foraminifers in ODP Hole 139-857A. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 2 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 1 records from Siphonaptera fossil - SMNG. 76124 records from Lichen field notes, Oslo (O). 52 records from Isotope tracer experiment: meiofauna counts. 1243 records from Crustacea ZMK. 19 records from Meiofauna abundance in sediment core 12930-036. 2820 records from (Figure 6) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-628A. 162 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 4012 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 86154 records from Naturalis Biodiversity Center (NL) - Coleoptera. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 355 records from Tag der Artenvielfalt. 47 records from Occurrence of mammalia relicts at site Burgtonna. 508 records from Planktic foraminifera abundance of Hole 23-222. 71 records from Foraminifera abundance of Hole 24-238. 441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 17720 records from Collection Polychaeta SMF. 271 records from Algae - Domestic Bacteria (KIDR-AG). 321 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 18970 records from Cowan Tetrapod Collection - Birds. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 151010 records from Marie-Victorin Herbarium (MT). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 84 records from BIRDRACE Vogelscheuchen. 26 records from Nannofossil abundance of Hole 37-332A. 127 records from BIRDRACE Southernmost Lakers. 52359 records from Iziko. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 8470 records from (Table 12) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-714A. 34 records from (Table 6) Temporal variations of relative abundance of dead cells (in detritus, conglomerates and associated with Probocsia alata) of total number of living and dead cells of Emiliania huxleyi at Stations AH-2001-B3 and AH-2001-B3A. 14 records from R. Curry Collection. 501 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 1 records from Arthropoden aus südostalpinen Höhlen.. 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 3413 records from Planktic foraminifera abundance of Hole 23-219. 40 records from Range table from planktonic foraminifers in ODP Hole 172-1063A. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1099A. 777 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 6 records from Pseudogramma xanthum, a new replacement name for a serranid fish from the subtropical South Pacific Ocean with description of the species.. 27940 records from HAS - Herbário Alarich Rudolf Holger Schultz. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 464 records from Lepidoptera collection, NTNU, Trondheim. 7956 records from NCOS (OBIS China). 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 20755 records from pins. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 582 records from Bioblitz 2013 Copenhagen Denmark. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 134 records from Birdrace-Team_Havelland-Havelland. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 16 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT008_5-CTD42. 21 records from Nannofossil abundance of Hole 19-192. 13884 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 438 records from (Table 3) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-653A. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 874 records from Flora acuática de Querétaro. 603 records from Polish Arctic Marine Programme (EurOBIS). 45 records from Occurrence of mammalia relicts at site Erdhöhle. 6328 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 126 records from Total foraminifera counts of multinet PO231/3_MSN1336. 2 records from Planktic foraminifera counts of multinet PS2616-5. 184 records from Abundance of calcareous dinoflagellates of sediment core GeoB3603-2. 10 records from Concentration of siliceous microplankton in surface sediments, size fraction 20-40 µm. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 2 records from Smear slide analysis of sediment core GeoB7427-2. 2 records from Nannofossil abundance of Hole 74-526. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 500 records from Plant (HBBG-PL). 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 24286 records from Ross A. Layberry Observations. 21 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 71 records from Occurrence of mammalia relicts at site Teufelsbrücke. 535 records from Benthic foraminifera abundance of Hole 73-522. 2353 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 1391 records from Lichen herbarium, NMBU. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Zetes longiusculus. 1808 records from Ant'Phipoda Database (New records). 13 records from (Table 14) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-668A. 6188 records from (Figure 1) Range chart of planktonic foraminiferal species at ODP Hole 107-654A. 245 records from Echuya Survey 2012. 399 records from CECT Spanish Type Culture Collection(Fungi). 337 records from Zooplankton of the Eastern South Pacific, Universidad de Guayaquil, Ecuador (OBIS South America, SOUTH PACIFIC NODE). 1086 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC17-98. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 9 records from Microplankton abundance at bottle station SEPT-1999-K8. 13 records from Planktic foraminifera abundance of Hole 60-460A. 14 records from Collection Pantopoda SMF. 13382 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 42 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 107 records from RSPB - Crested tit wintering survey in the UK, 1992-1995 (RSPB). 6081 records from UNR Herpetology. 2458 records from Colección de Ictiología. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 1 records from Miriapodi di alcune grotte della Campania. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 88018 records from NINA Vanndata øvrige arter. 101 records from (Table S1d) Measured tomographic parameters for Oridorsalis umbonatus during ETM-2 for ODP Holes 208-1263C and 208-1262A. 1 records from Fourmis récoltées à Madagascar, par le Dr. Conrad Keller.. 2963 records from MfN - Diptera Collection. 336 records from (Table T1) Calcareous nannofossil abundance estimates of ODP Hole 210-1276A.. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 458 records from Spiders_of_French_Guiana. 81 records from Birdrace-Die_Ornithomaten-Herford. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 2300 records from Botanical Society of the British Isles - Demonstration set of data downloaded from the BSBI threatened plant database. 3 records from Sarcodine counts and carbon biomass at station TT011_4-CTD46. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 4 records from Nannofossil abundance of Hole 31-293. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 84 records from Seawater carbonate chemistry and processes during experiments with phytoplankton Emiliania huxleyi (strain Bergen 2005), 2010. 32356 records from Actualización de la base de datos del Atlas Mastozoológico de México. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 98 records from Colección Nacional de Heliconias. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 609 records from Herbier L. Mulon (BOUM). 48 records from Pollen counts of sediment core GeoB9503-5. 25 records from Heavy minerals of sediment core PL94-08. 935041 records from NatureServe Network Species Occurrence Data. 1612 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 441 records from Planktic foraminifera distribution of sediment core 75KS76. 546 records from 20 Jahre Naturschutzgebiet Dreienberg. 3 records from Planktic foraminifera abundance of Hole 17-166. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 27290 records from Bird Monitoring Data. 12509 records from The Bat Conservation Trust - Hibernation Survey. 360 records from Küstenschutzwald. 4 records from Nannofossil abundance of Hole 29-284A. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 1184 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 5507 records from MAR - Herbário do Maranhão. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 1 records from Nothrus biciliatus. 8 records from Zoobenthos in surface sediments in the Yalta Bay. 4 records from Herpetology Collection. 2 records from Nannofossil abundance of Hole 66-489A. 52 records from Nannofossil abundance in sediment core PS1297-4. 67 records from (Table 2) Distribution of ostracodes in ODP Hole 107-650A. 7 records from Solifugae Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 129 records from Total foraminifera counts of multinet M12/3_MSN561. 122 records from Total foraminifera counts of multinet M21/2_MSN651. 1 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 8 records from Aktion des Romain-Rolland-Gymnasiums. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_6-CTD67. 2 records from Nannofossil abundance of Hole 1-4. 73821 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 42 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 1803 records from Vertebrate specimens of Jyväskylä University Museum. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 14605 records from DMNS Mammal Collection (Arctos). 287 records from BIRDRACE Pody und Co. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 113 records from Total foraminifera counts of multinet M21/2_MSN627. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-49. 140 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 322 records from Nannofossil abundance of Hole 15-147. 230 records from (Table 1) Relative abundance of benthic foraminifera in ODP Hole 112-679D. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 199 records from La fauna de Melolonthidae, Cerambycidae y Elateridae (Insecta: Coleoptera) de la reserva de la biósfera El Triunfo, Chiapas. 542 records from Planktic foraminifera abundance of Hole 18-175. 1099940 records from DOF 2001-2006. 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 25793 records from NCOS1959_Crustacea (OBIS China). 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 420 records from (Table 4) Relative abundances of planktonic foraminifera in Pliocene sediments of ODP Site 161-975 in the Mediterranean Sea. 160 records from Schulgelände Schule auf der Aue, Münster. 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 37 records from Planktic foraminifera abundance of Hole 29-279. 1322 records from Planktic foraminifera abundance of Hole 29-284. 14 records from Range table from planktonic foraminifers in ODP Hole 143-865B. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 767 records from Phytoplankton abundance in surface water in February 1998, Paita, Peru. 1578995 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 282 records from Deponie Klausdorf. 60 records from (Table 2) Quantitative parameters of the Emiliania huxleyi population at the section along 70 m isobath carried out on 26 and 27 August 2001. 7881 records from Algaterra Types. 2419291 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 44 records from "Schlechteberg" Ebersbach/Sa.. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 1 records from Streuobstwiese Alt Necheln. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 98 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1381. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 82 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 17 records from Taxonomy and distribution of the ant Cataglyphis setipes (Hymenoptera: Formicidae). 15 records from Meiofauna abundance in sediment core 54301-016. 3666 records from (Table 5) Stratigraphic ranges of selected Oligocene to earliest Miocene planktonic foraminifers in ODP Hole 115-709A. 32466 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 3 records from Analyses of the recent components of sediment core PS1010-1. 98 records from Occurrence of mammalia relicts at site Felsställe. 145 records from privater Garten. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 181724 records from ArtenFinder. 131 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 182-1127B. 19 records from (Table S2) Calcareous nannoplankton morphometric analyses performed of DSDP Hole 62-463 samples. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 113482 records from KUBI Ornithology Collection. 13909 records from Albany Museum. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 75 records from Foraminifera species abundances from tow TT007_8-MOC15. 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 1371 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 7 records from Nannofossil abundance of Hole 49-409. 138 records from (Table 2a) Species composition of planktonic foraminiferas in bottom sediments from Core AK6-434-1. 1035 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 48 records from Planktic foraminifera abundance of Hole 6-47. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 135656 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 632 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 3550 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 5 records from (Table T9) Calcareous nannofossil stratigraphy of ODP Hole 198-1211C. 184 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 51499 records from NRM-Fishes. 16282 records from Atlas der Raubfliegen Deutschlands - database. 3637 records from Lepidoptera collection of NW Europe. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 26835 records from Herbario Pontificia Universidad Javeriana. 99454 records from ICN - Herbário do Instituto de Ciências Naturais. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 51 records from Packer Collection / Xenochilicola bees, Chile. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 55 records from Seeufer ehem. BUGA-Gelände. 1649 records from MfN - Trace fossils. 153299 records from Insekten Sachsen. 1376 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 3 records from Nouvelles fourmis de Madagascar.. 1 records from Hypochthonius pallidulus. 358 records from (Appendix 3, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 25727 records from Irish National Badger Sett Database. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 191 records from Herpetofauna laguna El Tinije. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 111 records from Birdrace-Uhulogen-Lippe. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 7 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 3347 records from Mammal and Fish speciemens of Kumamoto City Museum. 40 records from Nannofossil abundance of Hole 21-205. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 142 records from (Appendix C) Average nannofossil abundances in mid-Pliocene sediments from the equatorial Atlantic. 4778 records from SO-Polylist. 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 327284 records from Fungi (S). 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 36459 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 134 records from Total foraminifera counts from M35/1_MSN1046. 166 records from Plasm bearing foraminifera counts of multinet M21/1_MSN610. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 13 records from Planktic foraminifera counts of multinet PS31/002. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2159-3. 46 records from Liether Park (LMS), 5a. 78 records from Nannofossil abundance of Hole 27-262. 39650 records from (Table T1) Miocene planktonic foraminiferal stratigraphy of ODP Hole 184-1148A. 1584 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 91 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-765C. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 407 records from Myriapoda - SMF. 4318 records from Diptera Collection of Museum and Institute of Zoology PAS. 113 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 11 records from Benthic macrofauna abundance of sediment core 13200-017. 134 records from Planktic foraminifera counts of sediment core V19-202. 1 records from Damaeus torvus. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 1395 records from Birds - Wild Birds (KIDR-BI). 3 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Frederike Proewe. 2310 records from (Table 15A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-593. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 333 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Charadriidae. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 6 records from (Table 1d) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the Late Neopleistocene - Holocene activity phase of the Keli Volcanic Highland. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 79186 records from All Ireland Non-Marine Molluscan Database. 73 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 56081 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 29362 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 11 records from Occurrence of mammalia relicts at site Rotselaar. 7 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 90 records from Range table from benthic foraminifers in ODP Hole 146-889B. 2794 records from Diversidad bentónica de la laguna Celestún, Yucatán. 9322 records from (Figure 3) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548A. 13842 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 205599 records from CABI Bioscience Fungus Collection. 677 records from Insect colletion. 568 records from Planktic foraminifera assemblage in sediment core SU92-21. 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 7 records from Analyses of the recent components of sediment core PS1402-2. 28 records from (Appendix A3) Paragloborotalia morphometric and coiling data from Oligocene sediments of ODP Site 199-1218 in the equatorial Pacific. 380 records from Artenvielfalt der Nordsee - Helgoland. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1092 records from Range table from planktonic foraminifers in ODP Hole 155-936A. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 178 records from RSPB - Corn bunting surveys on the Western Isles. 765 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 2312 records from Mycological collection of the National Museum. 1905 records from BioGIS - Reptiles - INPA database. 6 records from Fließgewässeruntersuchung am Haselbach. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 140 records from Distribution of planktonic foraminifera of sediment core SH1972_17. 2524 records from (Table 13) Ranges of benthic foraminifers through the early to middle Miocene in ODP Hole 115-715A. 1154 records from Collection Plecoptera - SMF. 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 1614 records from New Brunswick Museum Collection. 143811 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 1073 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 459 records from NSG Karwendel. 37 records from Range table from benthic foraminifers in ODP Hole 146-891A. 745 records from Gunma Museum of Natural History, Mammal Specimen. 13894 records from TEPB - Herbário Graziela Barroso. 9256 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 968 records from (Table T17) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P14-P18. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 (Araneae, Tetragnathidae) with notes on habits and conservation status . 36 records from Selz (Ingelheim am Rhein). 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 7380 records from University of Ghent - Zoology Museum - Invertebratacollectie. 79 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1375. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 3 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 6 records from Planktic foraminifera abundance of Hole 23-226. 850 records from RSPB - Crossbills, Distribution survey in Great Britain, 1995-2005 (RSPB). 154 records from Dermaptera in the icipe collection. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 33070 records from CSIRO Ichthyology provider for OZCAM. 1641 records from NCSM PaleoBotany Collection. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 124 records from Total foraminifera counts of multinet M21/1_MSN620. 153 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1909-2. 14 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 9 records from Abundance of radiolaria at station UT99-24-1. 2 records from Nannofossil abundance of Hole 3-17A. 8 records from Nannofossil abundance of Hole 49-412A. 4500 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 33 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 34 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 16 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 2 records from Wie viel Natur gibt es im Park?. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 16 records from Nannofossil abundance of Hole 24-235. 390 records from (Table 3) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Cismon core. 31 records from Pollen profile V and Ausfluss at Krumbach, Germany. 154124 records from Arizona State University Lichen Collection. 408 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 96489 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 275 records from Wald und Wiese am Buchwald. 1042 records from Planktic foraminifera abundance of Hole 37-333. 4132 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 1 records from Damaeus auritus. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cariamidae. 48 records from Nannofossil abundance in sediment core PS1314-4. 1309 records from Mongolian Plant (MMNH-PL). 18 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 32 records from (Table 4) Carbonate and washed residue weight percentages in ODP Hole 121-758B. 6 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 3477 records from Aves laguna El Tinije. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 12 records from Microplankton abundance at bottle station SEPT-1999-K4. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 15 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1256 records from Foraminifera abundance of Hole 64-481. 24 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 45 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 22998 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 302 records from Kohlstattbrunnental. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 122 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 663 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Lacewings and Allies (BNHS) - 1942-2009. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 20 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 764 records from BioGIS - Fish - INPA database. 19 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 123677 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 2 records from Nannofossil abundance of Hole 14-144A. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 1116 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 2178 records from Flora exsiccata Bavarica. 389 records from (Table 2) Distribution of planktonic foraminifera in DSDP Hole core 90-594. 5 records from Nannofossil abundance of Hole 6-53A. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 13616 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 958 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 177 records from Donauinsel des BN bei Entau. 4 records from MfN - Fossil vertebrates II. 214 records from Planktic foraminifera counts of sediment core V27-86. 1638 records from (Table 1) Relative abundances of benthonic foraminifera in ODP Site 116-717. 3772 records from Fish (KIWE-PI). 1185 records from (Appendix A) Foraminifera and stable carbon and oxygen isotope record of ODP Site 105-646. 5 records from Pollen record of a sediment profile from Lake Teletskoye. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 146624 records from Plants of Papua New Guinea. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1403-1. 1851 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 88 records from Microfossil abundance of Hole 16-157. 494 records from Biologische Station im Kreis Wesel. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 101 records from BIRDRACE nabu-rhein-main.de. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 238 records from Abundance of planktic foraminifera at CTD station PS55/081-1. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 19 records from (Table 2) Range chart of calcareous nannofossils from Maud Rise sediment cores. 950 records from (Table 9) Distribution of planktonic foraminifera in the early Pliocene to Holocene section of ODP Hole 149-900A. 51 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 185 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 7360 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 1445 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 2222 records from UWYMV Bird Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 53 records from BIRDRACE Taubenhaucher. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 138 records from Total foraminifera counts of multinet M11/1_MSN520. 152 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 12 records from Abundance of radiolaria at station LV28-44-1. 279 records from Koleopterologen am Bausenberg. 28 records from Smear slide analysis on sediment core GeoB4217-5. 101 records from Nannofossil abundance of Hole 64-476. 5 records from Nannofossil abundance of Hole 3-22. 2 records from Nannofossil abundance of Hole 74-525A. 219 records from (Table 2) Stratigraphic distribution of planktonic foraminifera from the middle Miocene to upper Miocene in ODP Hole 134-832B. 54 records from Planktic foraminifera abundance of Hole 15-146. 3304 records from Planktic foraminifera abundance of Hole 41-369A. 11 records from Oberservation of birds at station PS14/145 along 49° West. 819 records from (Table T4) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P7-P8. 14882 records from NCSM Mammals Collection. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 69 records from Faunal assemblage of sediment core GS7603-7. 7 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC6. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station SEPTEMBER-1995-D4. 36 records from Abundance of algae in the Aral Sea. 151 records from Planktic foraminifera abundance of Hole 11-104. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 1735 records from The Flora of County Clare. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 61 records from Wälder im Hainbachtal. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 76 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 2118 records from Flora de macroalgas del litoral oaxaqueño. 17369 records from MfN - Auchenorrhyncha Collection. 156948 records from NBI. 316 records from Moss species from Heard Island, 1987 and 2000. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 23 records from Planktic foraminifera abundance of Hole 29-284A. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 6 records from MfN - Micropaleontology. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 180 records from Phytoplankton abundance off Guañape islands in Juli 2003, Peru. 44 records from Flora und Fauna in unserer Kita. 43 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1017. 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 68304 records from IICT Herbário LISC. 2913345 records from Arthropods, Plants, Fungi, and other biodiversity of Costa Rica. 1695 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 258 records from BIRDRACE Raumpatrouille Oriolus. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 24 records from Counts (2) of calcareous dinocysts along profile Stevns-Klint. 933 records from (Table T3) Planktonic foraminifera abundance of ODP Site 170-1041 sediments. 7774 records from BioGIS - Hamaarag. 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 13 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 3318 records from ZOOLOGIA_FCNO_UDEC_CL Foraminiferos_01 (OBIS South America, SOUTH PACIFIC NODE). 176 records from INSECT COLLECTION. 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 18 records from Smear slide analysis on sediment core GeoB4206-1. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 260191 records from DINA. 65 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827A. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 1373 records from Finnish Entomological Database: Araneae. 4567 records from Herbarium WRSL, Main Collection. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 103 records from Wasserwerkspark (Chemnitz). 235 records from Total foraminifera counts from multinet M31/3_MSN905. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 27 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-50. 69 records from Naturpark Kottenforst-Ville 17.6.09. 349178 records from AMNH Herpetology Collections. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 290 records from Planktic foraminifera counts of sediment core RC11-134. 642 records from Planktic foraminifera counts of sediment core V22-196. 304 records from Planktic foraminifera counts of sediment core V29-173. 83 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Cumacea.. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 2084 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for sediment core R657. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 346511 records from ARGOS Satellite Tracking of animals. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 79 records from Occurrence of mammalia relicts at site Rislisberghöhle. 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 83 records from Planktic foraminifera abundance of Hole 40-361. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 2651 records from KTU Pteridophyta. 41717 records from Queen Victoria Museum Art Gallery provider for OZCAM. 49 records from New species of the amphiliid catfish genera Amphilius, Doumea and Phractura and the taxonomy of Paramphilius from West Central Africa (Siluriformes, Amphiliidae).. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 214 records from Benthos abundance in surface sediment sampled during cruise ANT-V/1. 1794 records from Elephant Seal Sightings, Heard Island. 29876 records from European Moth Nights. 1425 records from (Fig. 12) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 50-416A in the North Atlantic. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 5 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 1431 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 9558 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 3096 records from Biological Records Centre - Mosquito Recording Scheme. 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 261 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 1 records from Celaeno obsoleta. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 114 records from BIRDRACE VIE will rock you!. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 2 records from Benthic foraminifera abundance of Hole 42-376. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 1257 records from Faun. 40 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 7 records from (List 1) Fossil record of Mollusca in Schleswig-Holstein, Germany. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 106920 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 56302 records from Kathryn Kalmbach Herbarium. 1 records from Nothrus palliatus. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 54 records from Biotope im Schulumfeld. 38998 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 34 records from Foraminifera species abundances from tow TT007_9-MOC18. 134 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794. 4 records from Microzooplankton abundance and biomass at station TT054_17-21. 668 records from Phytoplankton abundance during OCEANIA cruise Oceania90. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 1 records from Nothrus convexus. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 133 records from Total foraminifera counts of multinet PO247/2_MSN1379. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 56 records from Nanoplankton abundance at station GeoB2021-3. 4 records from Nannofossil abundance of Hole 9-81. 823 records from Planktic foraminifera counts of sediment core V17-165. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 613 records from Distribution of dinoflagellate cycst at ODP Site 123-765 (Table 1). 2464 records from (Table 2) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-698A. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40 records from Öhmdwiesen und Göldern (Konstanz). 15 records from Urwald 2 (Bad Waldsee). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 227 records from Total foraminifera counts from multinet M31/3_MSN916. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 26 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 5817 records from SMNS Palaeontological collection - Amber. 4 records from Nannofossil abundance of Hole 77-540. 10898 records from Himenópteros Parasíticos en México (UANL). 1427 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 240 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 102 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 434 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 7551636 records from Birds Australia, Birdata. 2 records from Neue Milbenarten aus Kärnten. 1087 records from SMNS Palaeontological collection - Tertiary and quaternary invertebrates. 127 records from Birdrace_Schräge_Vögel-Herford. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 101 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 6 records from Nannofossil abundance of Hole 7-63. 12 records from Nannofossil abundance of Hole 74-528A. 2 records from Nannofossil abundance of Hole 58-442B. 137 records from Planktic foraminifera counts of sediment core V28-25. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/565-1. 15 records from Description of lithologic section units of IODP Hole 325-M0032A. 329 records from Fig. 11: Benthic foraminifera assemblage of sediment core MD97-2131. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 226 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 248 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 226 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 33 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ramphastidae. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 503 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Invertebrados. 1536 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 178 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 12829 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 6 records from Sediment properties of core PLG93_BCORE1. 582 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 166 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D2. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 5 records from Two new species of Exallonyx Kieffer (Hymenoptera: Proctotrupidae) from China, with a key to Chinese species.. 763 records from Bisons Collection. 213 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 311 records from Avena wild species VIR Herbarium. 3219 records from (Figure 6) Planktonic foraminifera distribution in ODP Hole 130-803D. 335 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 5 records from (Table 1) Late Maastrichtian calcareous nannofossils in DSDP Hole 22-212. 184156 records from The Flora of County Waterford. 17 records from MVZ Herp Observations (Arctos). 22854 records from National Botanic Garden Belgium - Myxomycetes. 88412 records from PACA-AGP - Herbarium Anchieta. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 1 records from Nothrus bicarinatus. 16324 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN889. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 38 records from Phytoplankton abundance at bottle station A1/52. 121 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 936 records from Bats of Poland. 288 records from Gorgonacea specimens of Kuroshio Biological Research Foundation. 20114 records from Molluscus specimens of Toyohashi Museum of Natural History. 16 records from Description of lithologic section units of IODP Hole 325-M0057A. 1789 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 2324 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 76 records from Live (Rose Bengal stained) benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 672 records from Colección de Entomología - Curculionidae. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 169 records from Expedition "Schulgelände". 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 198 records from Total foraminifera counts from M35/1_MSN1047. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 244 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 1726 records from KTU Pinophyta. 8 records from Nannofossil abundance of Hole 60-458. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 572 records from Planktic foraminifera counts of sediment core V04-32. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 3341 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 510 records from Planktic foraminifera counts of sediment core V20-242. 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 5 records from Range table from benthic foraminifers in ODP Hole 181-1120C. 345 records from Range table from nannofossils in ODP Hole 199-1218A. 872 records from Colección de Entomología - Hymenoptera - Parasitica. 180 records from Paul-Gerhardt-Schule Dassel. 66 records from Langes Tannen(LMS), Klasse 5d. 75 records from BIRDRACE Die Kartoffelsäcke. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 7414 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 23315 records from Gwaii Haanas Invertebrates (OBIS Canada). 4 records from Oribatids from Switzerland IX (Acari: Oribatidae, Mycobatidae 2) (Acarologica Genavensia CI). 1355 records from Planktic foraminifera abundance of Hole 18-173. 3509 records from Entocytheridae (Ostracoda) World Database. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 6649 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 1167 records from Macroinvertebrate Data BOKU. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 1 records from Occurrence of mammalia relicts at site Ejstrup. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 3 records from Nannofossil abundance of Hole 20-199. 12 records from Chenopodieae. 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 433 records from (Table S1) Palynology of IODP Hole 302-M0004A. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 123006 records from Finnish Entomological Database: Diptera. 17 records from (Table 2h) Nannofossil distribution chart of petroleum well Swan-3St. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 3422 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 9 records from (Table 4) Abundance of microalgae in sinking sedimentary material from sediment traps in the northeast Black Sea in September-October 1999. 497 records from Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1). 90 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 288 records from Planktic foraminifera abundance of Hole 94-610A. 48 records from Planktic foraminifera abundance of Hole 25-241. 35 records from Range table from planktonic foraminifers in ODP Hole 139-858D. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 138 records from Relative abundance of live benthic foraminifera of sediment core M5/2_107MC. 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 406 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 30409 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1069 records from ZFMK Sound Archive. 58031 records from Colección nacional de zoología. 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 17520 records from Arthropod collection, Tromsø Museum. 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 1 records from Hoplophora carinata. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 1 records from On the Chilopoda from Turkey. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 101 records from Birdrace-Herford-Birder-Herford. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 97 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1383. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 133 records from Abundance of planktic foraminifera at CTD station PS55/018. 4 records from Microzooplankton abundance and biomass at station TT054_26-21. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD59. 319 records from Dinoflagellate abundance of Hole 38-338. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 10061 records from Collembola collection of Arne Fjellberg, Norway. 8220347 records from OEH Atlas of NSW Wildlife. 231131 records from MVZ Mammal Collection (Arctos). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 126 records from BIRDRACE Die Schwenker-Birder. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 161 records from Total foraminifera counts of multinet M21/3_MSN671. 17876 records from Mycology Herbarium, Trondheim (TRH). 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 318 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 201 records from Mycological collections of the University of Tartu. 15663 records from Collection Herpetologie - SNSD. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 1309 records from Benthic foraminifera distribution of sediment core BP01-62/06. 13746 records from CNIN/Coleoptera. 83 records from Frau Voss. 92 records from Nottekanal, Klasse 7 - 10. 2 records from Range table from planktonic foraminifers in ODP Hole 139-855D. 255 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 73 records from Fossil (JNHM-FO). 4 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 482 records from Kühmark bei Wetzlar. 39 records from Ostracoda abundance of Hole 24-238. 4 records from Nannofossil abundance of Hole 5-32. 6 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 15918 records from BANDASCA, BAse de DAtos sobre SCArabaeidae. 128 records from (Table 5) Distribution of the large, many-chambered Globigerinelloides species in the Calabianca section. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 14830 records from Parasitic Platyhelminthes Collections. 102 records from Streuobstwiese RSG (Cham). 39 records from Planktic foraminifera abundance of Hole 28-265. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 66 records from Range table from planktonic foraminifers in ODP Hole 151-909A. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 871 records from Benthic foraminiferal assemblages (dead), surface data. 17966 records from Ornithology Collection. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 44443 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 9 records from Countryside Council for Wales - Sightings & Miscellaneous Data from Countryside Council for Wales (CCW), 2008 onwards. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 777 records from INRA-Versailles Arabidopsis natural variants. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 274 records from Bernhardsthal. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 199 records from Palynomorpha in sediment core PM9462-4 from the Laptev Sea. 6 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 5 records from Abundance of radiolaria at station LV28-66-1. 41884 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010). 81 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part I. 18 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE218. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 1 records from On the Chilopoda from Turkey. 1 records from Murcia ephippiata. 324 records from Total foraminifera counts from multinet M32/5_MSN974. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 9 records from Nannofossil abundance of Hole 26-255. 141 records from (Table 2) Relative abundance of benthic foraminifera in ODP Hole 112-680B. 364 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 180 records from Entdeckertour am Muldestausee. 20 records from Occurrence of mammalia relicts at site Niederlehme. 78 records from Range table from planktonic foraminifers in ODP Hole 167-1019C. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 1 records from Carabodes coriaceus. 76 records from Birdrace-Birding_for_Nature-Bonn. 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 34 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 7000 records from CCBER Ornithology Collection. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 51 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 105 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1372. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 8 records from Mean values of fractionated primary production and protozoan abundance from the photic layer collected at 50 m depth in Mejillones Bay. 46 records from Nannofossil abundance of Hole 26-254. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 12 records from Benthic macrofauna abundance of sediment core 13200-020. 1420 records from Planktic foraminifera abundance of Hole 49-407. 30 records from Range table from planktonic foraminifers in ODP Hole 152-916A. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 1 records from Dinoflagellates, pollen and spore abundance of Hole 29-281. 783 records from Phytoplankton abundance in surface water during cruise CD61. 46 records from Aktion Wiese und Wegrain Gitzenheide. 51 records from Coccoliths in sediment core PS1295-4. 47 records from Nannofossil abundance of Hole 86-577. 5 records from Nannofossil abundance of Hole 67-499B. 326 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 15 records from Abundance of Elminius modestus in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 3 records from Nannofossil abundance of Hole 9-80. 15 records from Benthic macrofauna abundance of sediment core 13077-093. 421 records from Planktic foraminifera counts of sediment core RC09-162. 599 records from Planktic foraminifera counts of sediment core V26-41. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station APRIL-1995-D4. 30 records from Occurrence of mammalia relicts at site Stematia. 14 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 822 records from Isotope tracer experiment: nematode abundance. 458 records from Barley French National Collection. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 50 records from Artensuche auf den Elbwiesen in Radebeul. 117 records from Naturschutzgebiet Kochertgraben. 77 records from Plasm bearing foraminifera counts from multinet SO119_MSN1303. 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 6 records from Microzooplankton abundance and biomass at station NBP97-03-09-1. 128 records from Phytoplankton abundance at station CD47_2805C#5. 544 records from (Table 1) Stratigraphic distribution of new marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B. 686 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 11700 records from (Figure 4) Distribution of benthic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 17979 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 900 records from Percentages of planktonic foraminifera species in sediment core V30-36. 171 records from Foraminifera abundance of sediment core C1960.201. 2698297 records from Eremaea. 3 records from Analyses of the recent components of sediment core PS1401-2. 626 records from (Table 2) Benthic foraminifera distribution in sediment core ASV11-880-3. 45 records from Pfrimmersbachtal. 152 records from Sonnentaugemeinschaft. 6 records from Planktic foraminifera abundance of Hole 4-24. 39 records from Range table from planktonic foraminifers in ODP Hole 139-856B. 255439 records from R. L. McGregor Herbarium Vascular Plants Collection. 94 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 3772 records from BOS Arthropod Collection of University of Oviedo (Spain): Opiliones. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1 records from Oribates picipes. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 86 records from Naturerlebnisraum Koppelsberg (Plön). 95 records from BIRDRACE BiBi. 1433 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 88 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2214-1. 42 records from Stadtwald Heide. 50 records from NABU-Fläche am Bösselhausener Weg. 69 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 225 records from Nannofossil abundance of Hole 15-154A. 47 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 414 records from (Table A a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-22 at 2000 m water depth. 12450 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 899 records from Collection Insecta fossil - SMF. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 81105 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 11 records from Microzooplankton abundance and biomass at station TT045_2-1. 18 records from Phytoplankton abundance at bottle station GOM3/1. 3 records from Nannofossil abundance of Hole 22-212. 13 records from Nannofossil abundance of Hole 94-607A. 666 records from (Table 2) Species composition of agglutinated foraminifers from the abyssal zone of the Pacific Ocean. 42 records from (Appendix 7) Abundance of Neogloboquadrina pachyderma in sediment core MD01-2444. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 950 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 580 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 109 records from Planktic foraminifera abundance of Hole 37-333A. 85 records from Range table from planktonic foraminifers in ODP Hole 151-909C. 41 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 56685 records from MISS_DC_01MAR2006. 1 records from The ant genus Pseudaphomomyrmex Wheeler, 1920 a junior synonym of Tapinoma Foerster, 1850.. 1101 records from Colección de Entomología - Orthoptera. 18 records from Thirteen new records of ferns from Brazil. 2413 records from Literature based species occurrence data of birds of North-East India. 10 records from Feuchtwiesen Wippertal bei Wippra. 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 125 records from Artenbestimmung. 44 records from Leegmoor (Moormerland/Leer). 617 records from Planktic foraminifera abundance of Hole 23-223. 145 records from Planktic foraminifera abundance of Hole 73-524. 689 records from Range table from planktonic foraminifers in ODP Hole 152-919B. 463 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 52 records from A new species of Cordyligaster Macquart, reared from caterpillars in Area de Conservacion Guanacaste, northwestern Costa Rica. 4 records from Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific.. 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 113 records from Tornoer Teich. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 11 records from Microzooplankton abundance and biomass at station TT043_28-1. 30 records from Phytoplankton abundance in surface water in 2001, Ancon, Peru. 27 records from Smear slide analysis on sediment core GeoB4212-2. 2 records from Nannofossil abundance of Hole 10-87. 129 records from Nannofossil abundance of Hole 29-284. 260 records from Range table from ostracoda in ODP Hole 144-873B. 1394 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 27 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 1620 records from (Figure 5) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-513. 150169 records from UWFC Ichthyology Collection. 2618 records from MAR-ECO (EurOBIS). 97 records from CNIN/Tipos Hymenoptera. 7014 records from (Figure 6) Distribution of planktic foraminifera of ODP Hole 159-958A. 10 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_996. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 4943 records from Collembola Collection. 378 records from (Figure 10) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-537. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 85 records from Birdrace-Die_Paradiesvögel-Herford. 229 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 284 records from Botanical collection of the National Museum. 16 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 74-527. 3 records from Planktic foraminifera abundance of Hole 54-424B. 4 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 2 records from Benthic foraminifera abundance of Hole 42-374. 56 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 1423 records from Raw counts of dinoflagellate cysts of sediment core DP30PC. 49 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 1. 14053 records from Herbarium Erlangense. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from LBV-Kindergruppen Markt Tussenhausen. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 6 records from Microzooplankton abundance and biomass at station NBP97-08-08-1. 10 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 4 records from Nannofossil abundance of Hole 10-89. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 19633 records from Natural History Museum Rotterdam (NL) - Chordata collection. 2072 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 8 records from Microzooplankton abundance and biomass at station NBP97-03-16-1. 2 records from Nannofossil abundance of Hole 1-1. 42 records from Ostracoda abundance of Hole 48-406. 1603 records from Fossil (MNHM-FO). 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 4 records from A new species of Tychobythinus Ganglbauer, 1896 (Coleoptera: Staphylinidae: Pselaphinae) from Turkey. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 815 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 133 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 4 records from Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River.. 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 805 records from Relativ abundances of live fauna of benthic foraminifera in surface sediments (Table C2.1). 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 72704 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 51 records from Coccolith counts of multinet M32/5_MSN971. 7 records from Nannofossil abundance of Hole 9-78. 13 records from Benthic macrofauna abundance of sediment core 12930-073. 14590 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 2288 records from (Table 2) Distribution of microfossils in the Barrow Group of ODP Site 122-763. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 539 records from Bay of Puck dataset (EurOBIS). 2115 records from Planktic foraminifera assemblage of sediment core ELT49.021-PC. 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 40 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 12 records from Occurrence of mammalia relicts at site Dolni Vestonice. 206 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 1 records from On centipedes (Chilopoda) of Albania, 2. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 254 records from BIRDRACE Thüringer Becken-Birders. 137 records from Planktic foraminifera counts at CTD station PS55/030. 25 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 53 records from Squid collection from 1995/96 V4 BROKE. 81 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE272. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 6050 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 1221 records from NBM Unionoids. 235 records from Klutensee. 1 records from Dinoflagellate abundance of Hole 38-343. 1 records from Abundance of benthos infauna at station GIK23038-1. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 2197 records from Benthic foraminifers of sediment core Svanic90_9004. 42507 records from Bird Collection of Museum and Institute of Zoology PAS. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 44 records from Solanum_baretiae. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 148 records from Total foraminifera counts from multinet SO119_MSN1278. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 169 records from Planktic foraminifera counts at CTD station PS55/051. 6 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 170 records from (Fig. 3) Relative abundance of Emiliania huxleyi in sediment core MD99-2343. 11459 records from Herbario de la Universidad de Sevilla, SEV-Historico. 1513 records from M. Gollop Collection. 40472 records from MEXU/Colección de Briofitas. 21593 records from CNCR/Colección Nacional de Crustaceos. 495 records from Life Science National Tsing Hua University. 9319 records from Itami City Museum of Insects. 1083 records from Percentages of planktonic foraminifera species in sediment core V29-144. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 213 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 58 records from Occurrence of mammalia relicts at site Sandalja II. 201 records from Planktic foraminifera abundance of Hole 4-31. 1047 records from Planktic foraminifera abundance of Hole 21-206. 196 records from Foraminifera abundance of Hole 33-317A. 102 records from Planktic foraminifera abundance of Hole 67-498A. 17400 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 102 records from Range table from benthic foraminifers in ODP Hole 139-858A. 14 records from (Tab. 7) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 43-384, J-Anomaly Ridge, Grand Banks off Nefoundland. 859 records from Royal Horticultural Society - RHS berberis sawfly (Arge berberidis) monitoring. 164 records from Terrestrial molluscs at the Natural Park of the Serralada Litoral (Barcelona, Spain). 150 records from Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk. 25592 records from Herbarium Amazonense. 1 records from Celaeno rhodomela. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 373 records from Otter survey of Ireland 2004 & 2005. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 26 records from Calcareous dinocysts in ODP Hole 80-550B, part 1. 9 records from Microzooplankton abundance and biomass at station TT043_11-1. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 6 records from Two new dolichoderine ant genera from Madagascar: Aptinoma gen. n. and Ravavy gen. n. (Hymenoptera: Formicidae).. 11 records from Nannofossil abundance of Hole 22-218. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 756 records from Targeting a portion of central European spider diversity for permanent preservation. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 22 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5116-2. 44 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 5 records from Trap data GBZ4, 696 m. 308 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 3 records from Nannofossil abundance of Hole 1-7. 3 records from Re-description of Cultroribula berolina Weigmann, 2006 (Acari, Oribatida, Astegistidae) from Germany with a key for the European species. 458 records from PeECE I - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway, 2001. 63 records from Planktic foraminifera counts of sediment core RC13-154. 55 records from "Schule am Inselsee" Güstrow. 1700 records from Nuevos registros de esponjas del Pacífico mexicano, Mar de Cortés y Archipiélago Revillagigedo. 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 1237 records from Nematode abundance in sediments obtained during RRS Charles Darwin cruise CD179. 1384 records from Bridel Herbar. 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 6 records from Occurrence of mammalia relicts at site Barova Cave. 2224 records from Cambridgeshire & Peterborough Biological Records Centre - Cambridge Lichen group data held by CPBRC.. 470 records from Phytoplankton abundance during Lev Titov cruise LT90/5. 319 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 5 records from Nannofossil abundance of Hole 29-278A. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 850 records from Riqueza específica y biogeografía de los corales hermatípicos de la sección sur del Golfo de California y las Islas Revillagigedo. 1157 records from ISU Mammals. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 1 records from Planktic foraminifera abundance of Hole 54-424A. 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 131 records from Siliceous microfossil occurrence, Site 177-1092. 5860 records from Loopkevers Grensmaas - Carabid beetles near the river Meuse in Flanders, Belgium. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 9 records from Numbers and dry weight of main macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 3). 864 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 4 records from Ostracoda abundance of Hole 32-305. 9 records from Nannofossil abundance of Hole 11-99A. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 48 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 64839 records from Mammals Specimens. 230 records from Pilularia Globulifera distribution map in Denmark. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 207 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 87 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 18 records from (Table 2) Average major-element composition of glass shards from Toba Tephra Beds in Sumatra, Malaysia, India, and the Indian Ocean. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 150 records from Vegetatively propagated Allium collection. 111 records from Planktic foraminifera abundance of Hole 9-79A. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 355 records from Culture Collection of Cryophilic Algae. 101 records from Naturgrundstück (Eutin). 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 371 records from Planktic foraminifera abundance of Hole 63-470. 27 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 38 records from Microfossil abundance of Hole 21-206C. 272 records from Dinoflagellate abundance of Hole 81-555. 420 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 132 records from tab 2. 1050 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 2500 records from Zooplankton (NSMK-ZP). 1 records from Arthropoden aus südostalpinen Höhlen.. 24972 records from Colección de Herbario. 100193 records from Mammalogy Collection - Royal Ontario Museum. 27 records from A new species of the gobiid fish Trimma from the Western Pacific and Northern Indian Ocean coral reefs, with a description of its osteology.. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 66081 records from HUFU - Herbarium Uberlandense. 10592 records from Wikander. 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 216 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 9879 records from Bibliographic records of Angola mammals. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 1 records from Oribates mollicomus. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 165 records from Total foraminifera counts from multinet M31/3_MSN898. 141 records from Plasm bearing foraminifera counts from multinet SO119_MSN1282. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 57 records from Heidesee / Halle. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 21 records from Bach. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 656 records from ZFMK Sound Archive. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 196 records from (Table 2) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 30-289. 3800 records from (Figure 7) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-630A. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 5815 records from Coleoptera of Białowieża Forest. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 4436 records from HUEG - Herbário da Universidade Estadual de Goiás. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 148 records from Faunal assemblage of sediment core GS7603-11. 13 records from Distribution of meiobenthos in sediment core M19_238-2 of the northeastern Atlantic (Table 1). 142 records from MfN - Fossil vertebrates I. 2 records from Nannofossil abundance of Hole 1-4. 6 records from Nannofossil abundance of Hole 10-91. 5 records from Nannofossil abundance of Hole 67-498A. 73 records from Nannofossil abundance of Hole 73-520. 11 records from Nannofossil abundance of Hole 11-101. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 2628 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Microzooplankton abundance and biomass at station TT050_4-7. 138 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV4. 9031 records from AIMS - LTM Nearshore Corals (OBIS Australia). 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 14 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 16 records from Occurrence of mammalia relicts at site Buchenloch. 15 records from Planktic foraminifera abundance of Hole 17-165. 1 records from Range table from planktonic foraminifers in ODP Hole 139-858F. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 28385 records from Plan de vertebrados de la Patagonia. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 25 records from Ostracoda abundance of Hole 48-404. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 128 records from Coccoliths in sediment core PS1535-8. 20672 records from MSB Parasite Collection (Arctos). 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 3420 records from Nova Scotia Museum of Natural History, Halifax, NS, Canada. 21680 records from Osaka Prefectural Minoh Park Insects Museum. 8684 records from Individual Sightings. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 39835 records from Lichen herbarium, Trondheim (TRH). 365 records from Greater Manchester Ecology Unit - Distribution of Bats in Greater Manchester. 2014 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 2091 records from Estudio florístico de las gramíneas de Zacatecas. 5186 records from Distribución conocida y potencial de 48 especies de hongos silvestres comestibles en la región central del país. 218 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D4. 22 records from Planktic foraminifera abundance of Hole 6-48B. 17 records from (Table 2) Distribution of Manumiella seelandica in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 33 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 14522 records from MVZ Egg and Nest Collection (Arctos). 60 records from crocodylus. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 68281 records from CU Invertebrate Paleontology. 976 records from (Table T2) Planktonic foraminifera abundance of ODP Site 170-1040 sediments. 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 76 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1214A. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 258 records from Planktic foraminifera abundance of Hole 40-364. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 17170 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 1 records from Arthropoden aus südostalpinen Höhlen.. 6 records from New country records of reptiles from Laos. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 104520 records from Recent Invertebrates Specimens. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 565 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 13 records from Range table from benthic foraminifers in ODP Hole 194-1192A. 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 779 records from Guadeloupe_Ananas. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 172 records from Total foraminifera counts of multinet PO247/2_MSN1371. 174 records from Birds (NHCA-BI). 127 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 244 records from Range table from benthic foraminifers in ODP Hole 145-887C. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 3082 records from dec2011. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 517 records from Schulzentrum "Parc Hosingen". 94 records from FFH-Gebiet Paartal. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_8-CTD102. 3718 records from Benthos counted on dredged samples during Valdivia cruise VA53. 30 records from Nannofossil abundance of Hole 94-608. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 103 records from (Table 6b) Calcareous nannofossil distribution on ODP Hole 117-731C. 436 records from Larval fish at Helgoland Roads in 2005. 1010 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 181 records from Marine Biological Association - RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 1447 records from Odonata of the Congo River 2010 expedition. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 5 records from Feuchtwiese. 38 records from Plasm bearing foraminifera counts of multinet M21/5_MSN742. 11 records from Distribution of meiobenthos in sediment core M19_232-2 of the northeastern Atlantic (Table 1). 23048 records from Herpetology Collection. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 51 records from (Table 1) Total cyst counts and concentrations of dinocysts and pollen together with environmental parameters. 37986 records from rmca-albertine-rift-cichlids. 80 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1361. 15 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1330. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 4 records from Microzooplankton abundance and biomass at station TT054_7-18. 9 records from Microzooplankton abundance and biomass at station NBP97-03-05-6. 641 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 242 records from Schieferbrüche. 110 records from Artenvielfalt und Kulturlandschaft. 40 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 1272 records from (Table 2) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-706A. 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 384824 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 1534 records from PonTaurus collection. 44 records from Planktic foraminifera abundance of Hole 19-188. 10 records from Oberservation of birds at station PS14/149 along 49° West. 140 records from Plant Living in Water (KIDR-PL). 81 records from Revision of the snailfish genus Allocareproctus Pitruk & Fedorov (Teleostei: Liparidae), with descriptions of four new species from the Aleutian Islands.. 10 records from Description of the females of Anapis castilla and Anapisona bordeaux (Araneae, Anapidae).. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 680 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 1496 records from Countryside Council for Wales - Stoneworts in Wales. 1030627 records from Phanerogamic Botanical Collections (S). 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 559 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Meiofauna. 655171 records from Bugbase, Lepidopterological Society. 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 165 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 43905 records from Herbarium of Jyväskylä University Museum. 35 records from Planktic foraminifera abundance of Hole 67-499A. 3210 records from HerbarioHerrerense. 58614 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 1017 records from Broadland Environmental Services Limited - Water vole distribution within Broadland (2003-2006): based upon field signs, sightings and trapping data.. 1 records from Abundance of benthos infauna at station GIK23062-2. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 13 records from Environment Agency - Environment Agency white-clawed crayfish Survey of the River Lune Catchment 2004. 510 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 10633 records from Biological Records Centre - Collembola Recording Scheme. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 83 records from Spechtwald. 174 records from BIRDRACE Bon(n)apartemöwen. 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 10 records from Occurrence of mammalia relicts at site Adler Cave xx. 40 records from Flächennaturdenkmal Grubditz. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 8 records from Abundance of radiolaria at station LV28-29-1. 29 records from Range table from ostracoda in ODP Hole 151-911A. 2048 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 108-659A. 1 records from Mesozoa - SMF. 3015 records from Bird specimens in Gifu Prefectural Museum. 1 records from Microfossil abundance of Hole 42-378. 5 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 1 records from Oribates fusifer. 1284 records from Collection of Heteroptera. 172 records from Leben im Finkensteiner Moor. 234 records from Baggerseen bei Krauchenwies. 1151 records from Coccolithophores in surface sediments of the Arabian Sea (TAble 1). 857 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 9 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE233. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 70 records from Korean Aquatic Vascular Plants. 4076 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 10 records from Ökowerk Emden. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD56. 3 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 21 records from Meiofauna abundance in sediment core 12930-018. 73 records from Planktic foraminifera counts of sediment core V24-28. 32 records from Grundschüler erkunden Schulumgebung. 54 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 33944 records from Aranzadi Zientzi Elkartea. 1359 records from GEO Biodiversity Day. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 25748 records from Diveboard - Scuba diving citizen science observations. 601 records from LBV 100 - Artenvielfalt am Rothsee. 138 records from Phytoplankton abundance at station DI182_11863#1. 2 records from Nannofossil abundance of Hole 9-82. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 14278 records from (Table 4) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-700B. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 9674 records from Mammal collection of National Museum of Nature and Science. 4550 records from University of Alberta Museums, Freshwater Invertebrate Collection. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 617 records from (Table 5) Realtive abundance of planktonic foraminifera in sediment core AHF-11343. 155 records from Bergbaufolgelandschaft am Muldestausee. 147 records from Planktic foraminifera abundance of Hole 22-217. 1177 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 323 records from Foraminifera abundance of sediment core IN68-29. 142 records from Birdrace-Alte_Socken-Cuxhaven. 9 records from Foraminifera abundance of Hole 64-477A. 11 records from A new species of Probolomyrmex from Madagascar.. 1756 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 593 records from Mamíferos voladores laguna El Tinije. 221 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 798 records from Biological Records Centre - Irish Otter Dataset. 91 records from CNIN/Tipos Homoptera. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D2. 237 records from Planktic foraminifera abundance of Hole 21-207. 88 records from Dinoflagellate abundance of Hole 28-274. 420 records from Phytoplankton abundance in surface water in January 1996, Ilo, Peru. 63 records from (Fig. 9A) Compiled data of profile L´Arboudeysse, SE France. 19 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 80 records from Planktic foraminifera abundance of Hole 49-411A. 569 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 1031 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-5. 149 records from Naturnahes Tal in Siena. 29 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 10 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2010. 448 records from Biodiverisity Group, Dept. of Environment, Food and Agriculture,Isle of Man Government - Japanese Knotweed Records in the Isle of Man 1991-2008. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 4 records from Range table from planktonic foraminifers in ODP Hole 171-1049A. 128 records from (Table 2) Distribution of ebridians and actiniscidians in selected samples from DSDP Hole 90-591. 33 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071F. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 1 records from Collection Mammalia fossil SMF. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 71 records from Birdrace-do_elster_Dortmund. 9 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_209-1. 11 records from Microzooplankton abundance and biomass at station TT045_15-2. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 380 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 218 records from GTI MICROFUNGI OBSERVATION. 34 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 2255 records from Plant Systematics Laboratory, Ajou University, Korea. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1 records from Nothrus canaliculatus. 25128 records from rmca-albertine-rift-butterflies. 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 111 records from BIRDRACE Die Wendehälse. 40 records from Plasm bearing foraminifera counts from M35/1_MSN1057. 491 records from Naturschutzgebiet Lüneburger Heide. 11 records from Nannofossil abundance of Hole 3-15. 2 records from Nannofossil abundance of Hole 3-18. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 60000 records from Birds (NSMK-BI). 206 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Herpetofauna. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 100125 records from Ohio State University Fish Division (OSUM). 197 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 74 records from Schulwald Grundschule Brügge. 12 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 2 records from Nannofossil abundance of Hole 1-5A. 336 records from Planktic foraminifera counts of sediment core V19-185. 601 records from Distribution of planktic foraminifera (112-200 µm) of sediment core M8_057-2 (Table 5). 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 2467 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 12 records from Schulgelände Erich-Kästner-Schule. 94 records from Total foraminifera counts from M35/1_MSN1074. 1 records from Microzooplankton abundance and biomass at station TT050_24-13. 11981 records from SMNK Mantid Collection. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 207 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 1088 records from Relativ abundances of total dead fauna of benthic foraminifera in surface sediments (Table C1.2). 281 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 4 records from Pycnogonida collection of National Museum of Nature and Science. 332 records from Foraminifera distribution of sediment core SDSE192. 149 records from Biotop Binsenwiesen (Wehrheim/Taunus). 685 records from Planktic foraminifera abundance of Hole 4-30. 63985 records from The First Atlas of Breeding Birds in Britain and Ireland: 1968-1972.. 59316 records from JPB - Herbário Lauro Pires Xavier. 850 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 389 records from Planktic foraminifera abundance of Hole 23-228. 36 records from Range table from benthic foraminifers in ODP Hole 160-967E. 1735 records from Naturalis National Natural History Museum (NL) – Acari_Types. 67371 records from Swedish Board of Fisheries (Fiskeriverket) - Swedish Electrofishing Registry. 534 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 48 records from Heider Bergsee (Brühl). 49 records from Total foraminifera counts of multinet M10/2_MSN238. 43 records from Nannofossil abundance of Hole 11-102. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 78 records from Occurrence of mammalia relicts at site Einhornhöhle. 8527 records from HSU Wildlife Birds. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 415 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 49 records from A catalogue of the ants of Paraguay (Hymenoptera: Formicidae).. 192 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 30926 records from Annelida collection of National Museum of Nature and Science. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 46 records from 8c. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 197 records from Total foraminifera counts of multinet M21/1_MSN608. 11 records from Phytoplankton abundance at station Sechin_2003-08-06_1, Casma, Peru. 1 records from Zetes dorsatus. 25830 records from Colección de Diatomeas del Sur del Golfo de México (ICMyL-DF, UNAM). 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 1 records from Oribates gilvipes. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 519292 records from Museum Victoria provider for OZCAM. 632 records from MVZ Hildebrand Collection (Arctos). 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 142 records from Total foraminifera counts of multinet M21/2_MSN649. 133 records from Total foraminifera counts of multinet PO231/3_MSN1334. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 141 records from Phytoplankton abundance at station CD47_3105C#4. 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 219 records from INERA-Luki reservation herbarium (CABIN project). 256 records from Planktic foraminifera counts of sediment core V16-20. 14 records from Relative abundance of live benthic foraminifera of sediment core M5/2_91MC. 16632 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 38 records from (Table 19) Nannoplankton distribution in sediment core ANS3-T9. 4288 records from Universitat de Girona: HGI-Cormophyta. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1429 records from Morano and Cardoso: AraIb. 164233 records from ORN. 7 records from Analyses of the recent components of sediment core PS1220-3. 224 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 39033 records from SBMNH Vertebrate Zoology. 26559 records from Taiwan Forestry Research Institute. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 7926 records from NBM birds. 298 records from Stausee (Oberdigisheim/Meßstetten). 89 records from Dixidae (Diptera) of Ireland. 3525 records from Countryside Council for Wales - Important Welsh Bat Roosts Database (BATSITES-WALES). 198044 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 13086 records from Collection of Coleoptera. 39 records from Südpark (Bochum-Wattenscheid). 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 2077 records from Vascular plant specimens of Iida City Museum. 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 4000 records from Fungal Collection of Natural History Museum and Institute, Chiba. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 87075 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 16 records from Phytoplankton abundance during Professor Siedlecki cruise PSied90/1. 24 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 759 records from Planktic foraminifera abundance of Hole 47-398D. 28 records from Planktic foraminifera abundance of Hole 31-301. 139 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 73 records from Benthic foraminifera abundance of Hole 80-550. 165 records from Foraminifera abundance of Hole 48-406. 162 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2039. 111991 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 101662 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 8 records from Krittenhorster Wald (Ostkilver). 164 records from Abundance of planktic foraminifera at CTD station PS55/066. 298 records from Results of palynological analysis of Hole 302-M0002A. 3946 records from EcoRecord - Amphibian records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 107 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 122 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 365 records from Colección Herpetológica de la Patagonia. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 1077 records from BioGIS - Fish - HUJ collections. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 117 records from Plasm bearing foraminifera counts of multinet M21/1_MSN619. 157 records from Total foraminifera counts of multinet M21/6_MSN787. 125572 records from NINA insect database. 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 1998 records from Institut Botanic de Barcelona, BC-Lichenotheca. 7 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 9 records from Distribution of hydropolyp species on coral reefs of the Red Sea (Table 5). 265 records from Geometry of coccolith Gephyrocapsa in sediment core K708-007. 2 records from Nannofossil abundance of Hole 20-199. 74 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 856 records from Planktic foraminifera counts of sediment core V27-178. 72316 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1993) (AfrOBIS). 12963 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 333 records from Langes Tannen (Uetersen). 22 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 3 records from Occurrence of mammalia relicts at site Igstadt I. 46 records from Palynomorph data and remarks on dominant tree taxa from IODP Hole 313-M0028A. 220 records from Foraminifera abundance of Hole 57-440. 247 records from Planktic foraminifera abundance of Hole 63-471. 121 records from Range table from planktonic foraminifers in ODP Hole 167-1011B. 23593 records from New Zealand Biodiversity Recording Network. 45841 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2004) (AfrOBIS). 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 11 records from Nannofossil abundance of Hole 55-431A. 232 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE278. 265 records from AIS Wildtype Populations of Arabidopsis. 17 records from (Table 3) Stratigraphic distribution of silicoflaggelates, ebridians and actiniscidians in upper Pliocene to Pleistocene sediments of ODP Hole 104-644A. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 103 records from Invertebrate collections. 62 records from Occurrence of mammalia relicts at site Pestera Livadita. 4196 records from Planktic foraminifera abundance of Hole 37-334. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD10. 14 records from Phytoplankton abundance during Arne Tiselius cruise AT90/1. 265 records from Luderbusch. 47 records from Nannofossil abundance of Hole 64-479. 574077 records from LACM Vertebrate Collection. 86 records from Pollen analysis of sediment core GIK16856-2. 150417 records from Natural History Museum, Vienna - Herbarium W. 5323 records from Anfibios y reptiles del estado de Nuevo León. 362 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 12 records from Abundance of microplankton from bottle APRIL-2000-K1. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 27 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 5 records from Nannofossil abundance of Hole 34-320A. 12 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 310 records from Planktic foraminifera counts of sediment core V18-191. 7 records from A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae).. 7 records from Grundschule Sandheide. 76 records from Fish (MNHM-PI). 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 5 records from Loricifera - SMF. 1868 records from Inventario florístico de la Sierra de San Carlos, Tamps. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 641 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 168582 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Lepidoptera Observation Records. Pre-2010 for Cumbria. 17413 records from Herbarium BSG Vascular Plants. 8 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 76 records from Occurrence of mammalia relicts at site Vindija. 4014 records from Herpetological specimens. 198 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 2511 records from (Table T5) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1052E. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 908 records from (Appendix A1) Planktonic foraminifera of ODP Hole 157-951A. 177494 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 894 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in core PS1243. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 20 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 145171 records from DUKE Bryophyte Collection. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 14212 records from MOSS - Herbário Dárdano de Andrade Lima. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 12321617 records from Norwegian Species Observation Service. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 92 records from Abundance of coccosphere-units of site GIK23259. 88 records from (Table 4) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-658A. 36 records from UC Davis Department of Anthropology Museum. 183 records from Schussenaue (Weingarten). 31 records from Planktic foraminifera abundance of Hole 76-534. 296 records from Planktic foraminifera abundance of Hole 67-499. 3 records from Dinoflagellates, pollen and spore abundance of Hole 29-284. 13545 records from Collection Bryozoa SMF. 62 records from (Appendix H) Benthic foraminifera groups in ODP Hole 172-1055B. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 1 records from 5. Wiener Gemeindebezirk. 65535 records from OAC-BIO Herbarium. 11 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 114 records from Range table from planktonic foraminifers in ODP Hole 171-1052F. 14 records from Benthic foraminifera abundance of Hole 96-620. 492 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 182 records from Relative abundance of live benthic foraminifera of sediment core M5/2_88MC. 2318 records from Fundación Miguel Lillo - Colección Ictiológica. 637 records from Countryside Council for Wales - Lamprey Survey Data. 41 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto129-136. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 10358 records from Census of the flora of Benin. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 36115 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 18 records from Landschaftsschutzgebiet Buchhorst2. 753 records from Range table from ostracoda in ODP Hole 144-872C. 14897 records from Rådgivende Biologer. 6 records from Bayerische Donau - Metten. 2392 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 968 records from TTRS Mammals. 1 records from Nothrus biurus. 23227 records from Mollusk data of Molltax, Norway. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 11 records from Pollen profile Märchenwald C, Harz, Germany. 20 records from Foraminifera abundance of Hole 58-442B. 2 records from Range table from benthic foraminifers in ODP Hole 139-858B. 100 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 64 records from (Table 3) Distribution of calcareous nannofossils in Cretaceous sediments recovered in ODP Site 129-801. 1900 records from Fungi Collection. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 25 records from Coccosphere-units of site GIK23414. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 5 records from Schulinnenhöfe (Gelsenkirchen). 366 records from Weinberg Reichersdorf. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 82 records from Plasm bearing foraminifera counts of multinet M27/2_MSN883. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 16 records from Dinoflagellate cysts of sediments core IOW211660-6. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_806-1. 1 records from Microplankton counts and carbon biomass at station TT007_8-CTD99. 3 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 45 records from (Table S2) Age determination of ODP Sites 202-1234 and 202-1235. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 757 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 3 records from Akita Prefectural Museum＋Millipedes Specimens of Akita Prefectural Museum. 103178 records from MfN - Heteroptera Collection. 126 records from (Table 2) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-703A. 6912 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 47 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 30246 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 48114 records from MMNH Museum Bird Collection. 479 records from CBS Bacteria Database. 763 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 2731 records from (Appendix B) Percentages, total flux and fragmentation index of planktic foraminifera for core T89-40, Walvis Ridge (SE Atlantic). 1 records from On the Chilopoda from Turkey. 94 records from Planktic foraminifera abundance of Hole 63-468A. 24 records from Range table from planktonic foraminifers in ODP Hole 146-889B. 876 records from Phytoplankton abundance in surface water in July-August 1996, Ilo, Peru. 324 records from Tentaculata collection of National Museum of Nature and Science. 250 records from BATS & The Millennium Link - Bat records associated with the Union and Forth & Clyde canals (Period 2000 to 2005). 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 63 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 387 records from Planktic foraminifera abundance of Hole 63-467. 4 records from Dinoflagellates, pollen and spore abundance of Hole 29-282. 14411 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 3471 records from Collection Foraminifera SMF. 589 records from (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea. 284 records from Collection Mammalogie - ZSRO. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 2880 records from Coleoptera, NEF. 31 records from Nationalpark Harz Schul-AG Braunlage. 26 records from Schulteich Heinrich-Mann-Schule. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 414 records from Naturschutzst
Keywords: GBIF; biodiversity; species occurrences